Eugenia Maleşevschi, the Bessarabian painter - 150 years from birth (Confluenţe Bibliologice, 2018)
The article deals with information on the life and activity of Basarabian painter Eugenia Maleşevschi (10.12.1868 - 26.10.1942) who represented the Moldavian art from the beginning of the 20th Century. On December 10, 150 years have passed since the birth of the painter.
Keywords: anniversary exhibition; Eugenia Maleșevschi (1868 - 1942); Bessarabian painters; collection of the USARB Scientiﬁc Library